2013
DOI: 10.1002/rcm.6716
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography/mass spectrometry analysis of the six‐ring regioisomeric dimethoxybenzyl‐N‐methylpiperazines (DMBMPs)

Abstract: The six regioisomeric dimethoxybenzyl-N-methylpiperazines yield equivalent fragment ions and deuterium labeling confirmed the elemental composition of the characteristic fragments in their mass spectra. Mixtures of the dimethoxybenzyl-N-methylpiperazines were successfully resolved via capillary gas chromatography using a relatively polar stationary phase and temperature-programming conditions. Copyright © 2013 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In a final step, the reaction of intermediate 32 with a series of commercial piperazines afforded products 1–10 , in a moderate to good yield (Scheme ). With the exception of products 1 and 10 , all molecules 1–29 from this work are described for the first time (Figure ) and they were all isolated as pure samples having analytical and spectroscopic data in good agreement with their structures (see Supporting Information ).…”
Section: Resultssupporting
confidence: 54%
“…In a final step, the reaction of intermediate 32 with a series of commercial piperazines afforded products 1–10 , in a moderate to good yield (Scheme ). With the exception of products 1 and 10 , all molecules 1–29 from this work are described for the first time (Figure ) and they were all isolated as pure samples having analytical and spectroscopic data in good agreement with their structures (see Supporting Information ).…”
Section: Resultssupporting
confidence: 54%
“…117 Dickson et al 118 reported that BZP, 3′-TFMPP and MCPP are present in ecstasy tablets since the former, in some nations, is a legal alternative to MDMA. 118 A wide array of analytical approaches have been reported by many different authors such as LC-MS, 24,119 capillary electrophoresis, 120 HPLC-fluorescence, 121 LC with diode array, 122,123 GC-MS [124][125][126] and chemiluminescence. 118 In 36% of the sample, drugs other than MDMA were found to be present; BZP, 3-TFMPP and MCPP were detected in 15%, 7% and 1% of the samples respectively.…”
Section: Piperazinesmentioning
confidence: 99%
“…118 In 36% of the sample, drugs other than MDMA were found to be present; BZP, 3-TFMPP and MCPP were detected in 15%, 7% and 1% of the samples respectively. 118 A wide array of analytical approaches have been reported by many different authors such as LC-MS, 24,119 capillary electrophoresis, 120 HPLC-fluorescence, 121 LC with diode array, 122,123 GC-MS [124][125][126] and chemiluminescence. 127 Arbo and coworkers 128 provided a thorough overview of piperazine compounds as drugs of abuse with the full range of analytical techniques and matrices applied, readers are directed to this paper.…”
Section: Piperazinesmentioning
confidence: 99%